2010
DOI: 10.1002/jcb.22570
|View full text |Cite
|
Sign up to set email alerts
|

PR‐Set7‐mediated monomethylation of histone H4 lysine 20 at specific genomic regions induces transcriptional repression

Abstract: Increasing evidence indicates that the post-translational modifications of the histone proteins play critical roles in all eukaryotic DNA-templated processes. To gain further biological insights into two of these modifications, the mono- and trimethylation of histone H4 lysine 20 (H4K20me1 and H4K20me3), ChIP-chip experiments were performed to identify the precise genomic regions on human chromosomes 21 and 22 occupied by these two modifications. Detailed analysis revealed that H4K20me1 was preferentially enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 54 publications
7
72
0
Order By: Relevance
“…During G2, we demonstrated that PR-Set7 is targeted primarily to specific heterochromatic regions of the genome, resulting in histone H4K20me1 (Congdon et al 2010). Importantly, PR-Set7-mediated H4K20me1 is required for cell cycle progression, as ablation of H4K20me1 results in a G2 arrest.…”
Section: Discussionmentioning
confidence: 89%
“…During G2, we demonstrated that PR-Set7 is targeted primarily to specific heterochromatic regions of the genome, resulting in histone H4K20me1 (Congdon et al 2010). Importantly, PR-Set7-mediated H4K20me1 is required for cell cycle progression, as ablation of H4K20me1 results in a G2 arrest.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, H4K20me1 may be related to somatic dosage compensation, which starts in early embryos and is fully established in L3s. H4K20me1 has been implicated in gene repression in Drosophila and human cells and is known to be associated with X inactivation in mouse cells (Nishioka et al 2002;Kohlmaier et al 2004;Congdon et al 2010). In humans, both H3K27me1 and H4K20me1 are found on actively transcribed regions (Barski et al 2007).…”
Section: Broad Chromatin Domains In C Elegansmentioning
confidence: 99%
“…However, RNAi-mediated reduction of SETD8 can increase the expression levels of specific target genes, and an increase in H4K20me1 levels by PHF8 knockdown reduces the mRNA levels of PHF8-bound genes (40,41,45). Additionally, tethering SETD8 to endogenous loci as well as to reporter genes results in mild repression of transcription (74). Finally, SETD8 depletion in flies is associated with position-effect variegation, a typical heterochromatin defect (75).…”
Section: Figmentioning
confidence: 99%